Odpowiedź :
[tex]f(x) = 3 ln x + ln(x^3)=3lnx+3lnx=6lnx[/tex]
Dziedzina:
[tex]x>0[/tex]
Funkcja jest rosnąca, jeżeli dla
[tex]x_1<x_2[/tex]
[tex]f(x_1)<f(x_2)[/tex]
[tex]f(x_1)-f(x_2)=6 ln x_1 -6 ln x_2=6(lnx_1-lnx_2)=6ln\frac{x_1}{x_2}[/tex]
---------------------
[tex]x_1<x_2\ \ \ |:x_2[/tex]
[tex]\frac{x_1}{x_2}<1[/tex]
[tex]ln\frac{x_1}{x_2}<ln 1[/tex]
[tex]ln\frac{x_1}{x_2}<0\ \ \ |\cdot6[/tex]
[tex]6ln\frac{x_1}{x_2}<0[/tex]
-------------------------
[tex]f(x_1)-f(x_2)<0[/tex]
[tex]f(x_1)<f(x_2)[/tex]
Funkcja jest rosnąca